International Trade’s Impact on Poverty - Gechev, Vasil (Research Papers, 2016)
International trade is one of the fastest developing sectors of the world economy, with total merchandise trade growing from 7.1 trillion in 1990 to 30.8 trillion in 2010. For the same period, the number of people living in extreme poverty (with under 1.25/day) worldwide has declined with nearly 800 million. This simultaneous growth of trade volumes and reduction of extreme poverty at macro level is the starting point of the analysis. Since a classical (mono-dimensional) ‘cause-effect’ relationship between trade and poverty cannot be identified, international trade’s impact on poverty has been examined through the static and dynamic effects of trade. The analysis features a broad empirical research, covering the regions with the highest concentration of extreme poverty – Africa, Asia and Latin America. The paper’s main thesis is that the long-term positive impact on poverty depends largely on the dynamic effects of trade.